Urbanization and green space dynamics in Greater Dhaka, Bangladesh - Byomkesh, Talukder; Nakagoshi, Nobukazo; Dewan, Ashraf (Springer Japan KK, 2012)
Green space is particularly indispensable for proper functioning of the ecosystem in an urban environment. This study was an attempt to dynamically map and monitor green spaces in Greater Dhaka of Bangladesh. Both primary and secondary data were acquired to document the spatial–temporal dynamics of green spaces in the study area. Using a supervised classification algorithm, multi-temporal land use/cover data were extracted from a set of satellite images. A number of spatial metrics were employed to understand the landscape condition in a multi-temporal manner. In addition, 50 key informants along with focus group discussion and observation techniques were used to document existing management aspects of green spaces and their conservation policies. The analysis revealed that green spaces in Greater Dhaka are rapidly disappearing over the course of time even though they provide a number of natural, economic and social benefits. The disappearance of green spaces was primarily attributed to a rapid increase in the urban population, mainly driven by rural–urban migration. As a result, the landscape became highly fragmented and less connected. A substantial reduction of green patches is also leading to deterioration of the ecological condition of the landscape. The drastic reduction of green spaces in Greater Dhaka has been attributed to a lack of policy, low political motivation, and poor management. In order to ensure sustainability of green spaces and proper functioning of the city’s ecosystem, there is an urgent need for strategic green space planning.